Solid-liquid equilibria in relevant subsystems of LiBr-NaBr-KBr-MgBr2-CaBr2-H2O system at 298.15 K - Cui, Ruizhi; Peng, Changwei; Nie, Guoliang; Sang, Shihua; Ren, Hongbao; Li, Wu (Frontiers in Chemistry, 2023)
In view of the composition characteristics of lithium, calcium and bromine rich in Nanyishan oil and gas field brine of western Qaidam Basin, Qinghai Province, as well as based on the results reported in relevant literature, the phase equilibrium relationship of ternary system LiBr-CaBr2-H2O at 298.15 K was studied by isothermal dissolution equilibrium method. The equilibrium solid phase crystallization regions, as well as the compositions of invariant point, in phase diagram of this ternary system were clarified. On basis of the above ternary system research, the stable phase equilibria of quaternary systems (LiBr-NaBr-CaBr2-H2O, LiBr-KBr-CaBr2-H2O and LiBr-MgBr2-CaBr2-H2O), as well as quinary systems (LiBr-NaBr-KBr-CaBr2-H2O, LiBr-NaBr-MgBr2-CaBr2-H2O and LiBr-KBr-MgBr2-CaBr2-H2O) were further carried out at 298.15 K. According to the above experimental results, the corresponding phase diagrams at 298.15 K were drawn, which revealed the phase relationship of each component in solution and the law of crystallization and dissolution, and meanwhile summarized changing trends. The research results of this paper lay a foundation for further research on the multitemperature phase equilibria and thermodynamic properties of lithium and bromine containing high-component brine system in later stage, and also provide basic thermodynamic data for guiding the comprehensive development and utilization of this oil and gas field brine resource.